Seven Sisters: a mission to study fundamental plasma physical processes in the solar wind and a pathfinder to advance space weather prediction - Nykyri, Katariina; Ma, Xuanye; Burkholder, Brandon; Liou, Yu-Lun; Cuéllar, Roberto; Kavosi, Shiva; Borovsky, Joseph E.; Parker, Jeff; Rosen, Mitchell; De Moudt, Lauren; Ebert, Robert Wilkes; Ogasawara, Keiichi; et al. (Frontiers in Astronomy and Space Sciences, 2023)
This paper summarises the Seven Sisters solar wind mission concept and the outstanding science questions motivating the mission science objectives. The Seven Sisters mission includes seven individual spacecraft designed to uncover fundamental physical processes in the solar wind and provides up to $≈$ two days advanced space weather warnings for 550 Earth days during the mission. The mission will collect critical measurements of the thermal and suprathermal plasma, and magnetic fields utilizing for the first time Venus-Sun Lagrange points. The multi-spacecraft configuration makes it possible to distinguish between spatial and temporal changes, define gradients and quantify cross-scale transport in solar wind structures. Seven Sisters will determine the 3-D structure of the solar wind and its transient phenomena and their evolution in the inner heliosphere. Data from the Seven Sisters mission will allow identifying physical processes and quantifying the relative contribution of different mechanisms responsible for suprathermal particle energization in the solar wind.